2010
DOI: 10.1016/j.ejogrb.2010.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of adult female stress urinary incontinence: guidelines for clinical practice from the French College of Gynaecologists and Obstetricians

Abstract: Urinary incontinence is a frequent affliction in women and may be disabling and costly {LE1}. When consulting for urinary incontinence, it is recommended that circumstances, frequency and severity of leaks be specified {Grade B}. The cough test is recommended prior to surgery {Grade C}. Urodynamic investigations are not needed before lower urinary tract rehabilitation {Grade B}. A complete urodynamic investigation is recommended prior to surgery for urinary incontinence {Grade C}. In cases of pure stress urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 11 publications
0
51
0
10
Order By: Relevance
“…This is because low MUCP and functional urethral length during preoperative urodynamic evaluation are significant predictors for occult SUI (19). In contrast, another consensus showed detection rate was lower with pessary than with speculum prolapse reduction (20).…”
Section: Discussionmentioning
confidence: 65%
“…This is because low MUCP and functional urethral length during preoperative urodynamic evaluation are significant predictors for occult SUI (19). In contrast, another consensus showed detection rate was lower with pessary than with speculum prolapse reduction (20).…”
Section: Discussionmentioning
confidence: 65%
“…[2,5,6] The procedure is a minimally invasive intervention, nevertheless, voiding dysfunction, infection, pain, skin infection, and erosion,and bladder injuries can be seen. [7] In a study performed by Demirkesen et al [7] the authors observed voiding dysfunction (n=3), and painful urination (n=3) in their 85 patients who had undergone TOT operations.…”
Section: Discussionmentioning
confidence: 99%
“…Однако при наличии симптомов ГМП у женщин в постменопаузе на-значение вагинальных форм эстрогенов целесообразно и патогенетически обосновано [42,43].…”
Section: треугольник льето 40unclassified